O Serviço Social na educação básica: navegando entre rios e florestas no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The study put at the center of the debate the professional work of social workers in the Education Policy, which is built in the middle of rivers and forests of the state of Amazonas, with the general objective of analyzing the work of social workers in the Education Policy in the municipalities of the interior of Amazonas, considering the particularities of the social issue in the Amazon Region, and as specific objectives: to unveil the expressions of the social issue that require the work of social workers in Basic Education in the interior of the state; characterize the socio-occupational spaces in which social workers work in the different federated entities in the interior of the Amazon; and, to apprehend the attributions, competences, demands and responses of social workers within the scope of the Basic Education Policy Amazonian. The research had a theoretical and methodological contribution through historical and dialectical materialism and as analytical categories: totality, contradiction, mediation, and the triad universality, particularity, and singularity. The nature of the research was explanatory, and the methodological approach chosen was the mixed approach, that is, with the use of qualitative and quantitative data. The research had a bibliographic, documentary and field design, which was developed to build the theoretical foundations of the work, such as the social issue in the Amazon, Social Work in basic education and the work of social workers. The collection instrument was a questionnaire with open and closed questions, through the Google Forms tool, whose valid link was sent to the research subjects. In relation to the universe of the research, 96 social workers working in basic education in the 61 municipalities of the interior of the state were mapped, with the option of excluding the capital Manaus. Of the universe, 75 professionals responded, corresponding to a sample of 78%. The research reveals the great need to consider the regional particularities of the Amazon in the development of public policies and professional work. Therefore, it is essential to identify the sociocultural aspects that direct the life of the various groups or social segments that live in the Amazon to carry out a more concrete evaluation/analysis of the social reality. The research sought to unveil the expressions of the social issue present in basic education in the state, which will enable appropriation and professional deepening through a critical intervention on the expressions of the social issue in the Amazon. The expressions of the social issue present in the Amazonian educational scenario are child labor, difficulty of access to the services of other public policies, lack of school transportation, violation of the rights of children and adolescents. Social workers who work in basic education still have difficulty perceiving the socio-environmental and cultural particularities of the Amazon region in the apprehension of the expressions of the social question. The regional particularities are not restricted only to floods, ebbs, and flows, which are part of the socio-environmental issue, we also have border relations and migratory flows; food insecurity; ethnic-racial discrimination and violence and sexual exploitation, among others. The dissertation explains the urgency that the regional particularities of indigenous and traditional peoples are apprehended and considered in the planning, execution, and evaluation of public policies in the Amazon, especially education policy.
Social Work in basic education: sailing between rivers and forests in the Amazon
Keywords: .; .; .; CIENCIAS SOCIAIS APLICADAS; Questão social na Amazônia; Trabalho do(a) assistente social; Serviço Social na Educação; Educação Básica; Particularidades regionais